PENGARUH KEBIJAKAN PROMOSI TERHADAP LOYALITAS PELANGGAN KARTU PASCA BAYAR MATRIX PADA PT. INDOSAT DI BANDAR LAMPUNG - Rahayu, Mieke (Jurnal Manajemen dan Keuangan, 2010)
The determine policies promotion by PT Indosat in Matrix card marketing are personal contact and direct mail. Although two kind of campaigns are carried out but does not increase the percentage of customer matrix volume. The purpose of this study was to measure the influence of promotion toward the customer postpaid matrix card loyalty at PT.Indosat in Bandar Lampung. Research methods used in this research is descriptive quantitative method. Population in this research are customer or matrix card user in Lampung, on the year 2009 were 186 803 subscribers. The total sample of 100 respondents estimated through accidental Slovin sampling techniques. Data analysis techniques used are simple linear regression model and t test.Results showed that the regression equation y= 25,99 + 0,493X, the customer loyalty will still have value 25.99 without affecting variables of promotions and customer loyalty will increase by 0.493 where promotion policy is also increased by one. Degree of correlation between customer loyalty promotion policy with the level of closeness is (R= 0,486). Magnitude relationship with customer loyalty promotion policy is 23,7 % (R2 = 0,237). There is a significant influence of promotion toward the customer postpaid Matrix card loyalty at PT Indosat in Bandar Lampung (t count>t table = 5,511 > 1,662).Keyword: Policies Promotion (personal contact, direct mail) and customers loyalty